Factor Related to Depression in Type 2 Diabetic Patients in Nong Muang Khai District, Phrae Province. - Lokkhamlue, Thanapong; Chainan , Kanika; Saengduang , Niphitphon (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
This research aimed to investigate 1) the prevalence of depression among Type 2 Diabetes, and 2) identify factors associated with depression in this population. The study focused on a sample of 285 Type 2 diabetic patients undergoing outpatient treatment at Nong Muang Khai Hospital in Phrae Province. The research instruments were the general information questionnaire, the Perception of Health status questionnaire, and the 9-question depression assessment. The content validity index was 0.67-1.00, and Cronbach's alpha reliability test yielded a score of 0.74-0.82. Data were analyzed using descriptive statistics, chi-square test and logistic regression analysis. The findings revealed a 21.40 percent prevalence of depression among Type 2 diabetes patients at Nong Muang Khai Hospital in Phrae province. Factors that were significantly related to depression in patients with type 2 diabetes at the 0.05 level are gender, having other comorbidities, and duration of diabetes. Factors that have a negative relationship with depression with a statistical significance at the 0.05 level was the adequacy of income. Consequently, the proposed guidelines for preventing depression in Type 2 diabetes patients recommend regular assessment and monitoring, particularly among female patients, those with insufficient income, individuals with other co-morbidities, and those who have been diabetic for a decade or more.